Cystic Form of Duodenal Dystrophy (Clinical Case) - D. E. Okonskaya; Kh. H. Ayvazyan; Yu. A. Stepanova; A. V. Zhao; E. A. Sokolova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: the reason for the publication was the rare occurrence, as well as the non-specificity of symptoms of the cystic form of duodenal dystrophy. The listed features of this disease lead to difficulties in its differential diagnosis and the choice of the optimal method of treatment.General statements. The report is devoted to the description of a case of successful treatment of a cystic form of duodenal dystrophy — a chronic inflammation of the pancreatic tissue, ectopic in the wall of the duodenum. A 47-year-old patient was admitted to the clinic with complaints of persistent abdominal pain, periodic vomiting, general weakness, weight loss of 20 kg in three months. With the help of computed tomography, the diagnosis was established, the tumor process was rejected, and chronic pancreatitis was detected in the orthotopic pancreas. Due to the presence of changes in the main pancreas, the patient underwent pancreatoduodenal resection. The features of the operation were pronounced infiltrative changes and pronounced vitreous tissue edema, which made it difficult to mobilize the hepatic flexure of the colon and duodenum.Conclusion. Pancreatoduodenal resection is the optimal surgical intervention for the combination of cystic form of duodenal dystrophy with sub-/decompensated duodenal stenosis.